Challenges and Emerging Trends in Toner Waste Recycling: A Review - Meera Parthasarathy (Recycling, 2021)
Toner waste is one of the major electronic waste materials posing serious environmental threat and health hazards. Globally, only about 20–30% of toner waste is recycled, while the remaining percentage is dumped in landfills. Recycling options are limited due to the desirably engineered durability of toners, ascribed to a complicated composition of chemicals, carbon black, and plastic particles, which in turn creates critical challenges in recycling. The World Health Organization has classified toner waste as class 2B carcinogen due to its potential health hazard. In this review, the existing challenges in toner waste recycling are discussed from the perspective of environmental, health, and feasibility aspects. In parallel, the challenges have been opening up alternative strategies to recycle toner wastes. Emerging trends in toner waste recycling include transformation of toner waste into value-added products, utilization as raw material for nanomaterial synthesis, generation of composite electrodes for power generation/storage devices, integration into construction materials, and development of microwave absorbing composites. Considering the enormous volume of toner waste generated globally every year, better recycling and transformation strategies are needed immediately. A circular economy could be established in the future by transforming the enormous toner waste into a resource for other applications. For an effective management of toner waste in the future, an integrated approach involving policies and legislations, infrastructure for collection and treatment, and financial planning among the stakeholders is needed in addition to technological innovations.